Video Animasi Sebagai Media Edukasi Pengetahuan Dietary Approaches To Stop Hypertension Pada Kader Lansia - Yanuar Henus Pratama; Mizam Ari Kurniyanti; Muntaha . (Media Husada Journal Of Nursing Science, 2026)
Abstract Hypertension is a leading health problem among the elderly, and community health cadres play a crucial role in providing education for its prevention. The DASH (Dietary Approaches to Stop Hypertension) diet is an evidence-based approach to reduce hypertension risk, yet knowledge gaps remain among elderly health cadres. This study aimed to analyze the effectiveness of animated video-based health education in improving elderly health cadres’ knowledge about the DASH diet. A quasi-experimental design with a pretest–posttest control group was used, involving 56 cadres divided equally into intervention (n=28) and control (n=28) groups through total sampling. Knowledge was measured using a 16-item questionnaire. Data were analyzed with paired t-tests and independent t-tests. Results showed a significant increase in the intervention group’s mean score from 12.57 (pretest) to 14.64 (posttest) with a mean difference of 2.07 points (p=0.003), whereas the control group improved only from 11.96 to 12.78 (difference 0.82; p=0.026). Independent t-test revealed a significant posttest difference between groups (p=0.001). The findings indicate that animated video is an effective educational tool to enhance cadres’ knowledge of the DASH diet and can be implemented as an innovative strategy in community-based hypertension prevention programs. Keywords: Health education, animated video, DASH, elderly health cadres, hypertension.